2016
DOI: 10.1108/maj-08-2013-0910
|View full text |Cite
|
Sign up to set email alerts
|

Internal control effectiveness – a clustering approach

Abstract:  Purpose: Internal control frameworks provide only broad guidance concerning internal control concepts, leaving the details to the adopting firms. In this study the adopted internal control structure and effectiveness in firms is examined and visualized, and a typology of firms is presented. Control structure and effectiveness are measured based on the assessment of management, rather than using reported material weaknesses as most studies do. This type of evaluation is more purposeful for firms that do not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 57 publications
3
39
0
4
Order By: Relevance
“…Secondly, this result also supports studies that advocated the importance of internal control as one of the factors influencing corruption (Ge et al, 2014;Feng et al, 2015;Cheng et al, 2013;Ashbaugh-Skaife et al, 2008;Sun, 2016;Lansiluoto et al, 2016). The findings show that there is a high influence of internal controls towards corruption.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Secondly, this result also supports studies that advocated the importance of internal control as one of the factors influencing corruption (Ge et al, 2014;Feng et al, 2015;Cheng et al, 2013;Ashbaugh-Skaife et al, 2008;Sun, 2016;Lansiluoto et al, 2016). The findings show that there is a high influence of internal controls towards corruption.…”
Section: Resultssupporting
confidence: 85%
“…Prior literatures found that there is negative relationship between internal control and corruption. Weak internal control is susceptible to corporate corruption (Ge et al, 2014), it also increase the probability of management to practice corruption and make the organization unreliable in the eyes of investors (Lansiluoto et al, 2016;Umaru & Ombugus 2017) and create negative impact on the organization (Sun, 2016). In addition, other studies found that when strong internal controls are adopted in the organization, it will likely improve the investment decision (Cheng et al, 2013), increase the firm"s operating efficiency and performance (Feng et al, 2015), reduces the unintentional errors in the financial reporting and consequently, a more accurate financial input is achieved and corruption is reduced (Ashbaugh-Skaife et al, 2008).…”
Section: Internal Control and Corruptionmentioning
confidence: 99%
“…Therefore, the objective of an effective internal control system is to provide an assurance that a bank is efficiently and effectively directing its operations according to its mission statement, that its management data and financial reporting are dependable, and that it advances in compliance with applicable laws and regulations. If a bank does not have a viable internal control system, it is conceivable that it could be vulnerable [31]. Internal control is now linked to risk management.…”
Section: Internal Controlmentioning
confidence: 99%
“…Enterprises need to avoid the risks existing in the market as far as possible to gain a foothold in a fast-growing society and achieve better economic benefits; for this, the business-related internal controls need to be done well. The effectiveness of internal control of an enterprise is not isolated in the development process of the enterprise, but is linked to the specific control objectives of the enterprise and related control processes [2]. If the internal control of an enterprise wants to be effective, the specific process of control needs to provide a reasonable and scientific guarantee for the control objective to be achieved.…”
Section: Introductionmentioning
confidence: 99%